2021
DOI: 10.1155/2021/9943465
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of an Autophagy-Related Prognostic Model for Osteosarcoma Patients

Abstract: While the prognostic value of autophagy-related genes (ARGs) in OS patients remains scarcely known, increasing evidence is indicating that autophagy is closely associated with the development and progression of osteosarcoma (OS). Therefore, we explored the prognostic value of ARGs in OS patients and illuminate associated mechanisms in this study. When the OS patients in the training/validation cohort were stratified into high- and low-risk groups according to the risk model established using least absolute shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Based on the identified glutamine metabolism-related genes in osteosarcoma, a sixteen-gene signature was discovered by LASSO regression analysis. Unlike studies of previously reported prognostic models for osteosarcoma, such as models using autophagy-related genes, 17 super enhancer-related genes, 18 and immune-related genes, 19 , 20 our study was the first to use two external validation datasets rather than only one validation cohort to evaluate the model’s predictive accuracy, which is expected to substantially improve the model’s reproducibility and generalizability to new and different patients. Most importantly, the risk score calculated from the sixteen-gene signature had excellent performance in predicting the three- and five-year OS probabilities for all of the available osteosarcoma datasets in the GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the identified glutamine metabolism-related genes in osteosarcoma, a sixteen-gene signature was discovered by LASSO regression analysis. Unlike studies of previously reported prognostic models for osteosarcoma, such as models using autophagy-related genes, 17 super enhancer-related genes, 18 and immune-related genes, 19 , 20 our study was the first to use two external validation datasets rather than only one validation cohort to evaluate the model’s predictive accuracy, which is expected to substantially improve the model’s reproducibility and generalizability to new and different patients. Most importantly, the risk score calculated from the sixteen-gene signature had excellent performance in predicting the three- and five-year OS probabilities for all of the available osteosarcoma datasets in the GEO database.…”
Section: Discussionmentioning
confidence: 99%